Bacteriocinogenic effect of Lactobacillus sakei 2a on microbiological quality of fermented Sardinella brasiliensis - Espírito Santo,Milton L. P. (2003)
Lactobacillus sakei 2a is a bacteriocin producer strain and, in this work, it's effects as a starter culture in the fermentation process of sardine (Sardinella brasiliensis) fillets were observed at different concentrations of NaCl (2, 4 and 6%) and glucose (2 and 4%), to determine it's ability to produce organic acids and consequent pH reduction. Experiments were carried out independently, with only one parameter (NaCl or glucose) varying at a time. After 21 days of fermentation the deteriorative bacteria concentration reached 9.7 Log10 CFU. g-1 corresponding to 6% NaCl and 4% glucose. Little differences were observed in lactic acid production when 2 and 4% glucose were added, since total acidity was 1.32 and 1.34% respectively, the experiments with 6% NaCl presented the best results. Initial pH of sardine fillets was 6 and after 21 days pH values were 3.8, 3.9 and 4 for the experiments with 2, 4 and 6% NaCl. This may have been due to the inhibitory properties of NaCl over the deteriorative bacteria. After 21 days of the fermentation process lactic acid bacteria concentrations were 14.5 Log10 CFU.g-1. The ratio protein nitrogen and total soluble nitrogen was typical of a cured fish.